(untitled) (Makerere University Journal of Agricultural & Environmental Sciences, 2020)
Although food and nutritional security is at the heart of Uganda’s development agenda, it remains a core challenge partly due to the failure of interventions to recognize the direct linkages between land tenure and food security. This paper reviews land tenure as a dynamic concept in enhancing social and economic development with direct impacts on food and nutritional security of Uganda’s agriculture-based economy. Such direct impacts could have nation-wide food security policy implications. Where land tenure reforms result in inequitable distribution of land, they render vulnerability to food insecurity to marginalized categories. Appropriate tenure reforms have the potential to enhance land investments, develop markets, improve agricultural productivity, and provide revenue for landless households resulting into decreased malnutrition. Deliberate efforts to align food security policy with land tenure policy are critical weapons in the fight against food and nutritional insecurity in order to keep the hope and future of Ugandans alive.